Sustainable Utilization of Metals: Processing, Recovery and Recycling - Friedrich, Bernd (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The high demand for advanced metallic materials raises the need for an extensive recycling of metals and such a sustainable use of raw materials. ""Sustainable Utilization of Metals - Processing, Recovery and Recycling"" comprises the latest scientific achievements in efficient production of metals and such addresses sustainable resource use as part of the circular economy strategy. This policy drives the present contributions, aiming on the recirculation of EoL-streams such as Waste Electric and Electronic Equipment (WEEE), multi-metal alloys or composite materials back into metal production. This needs a holistic approach, resulting in the maximal avoidance of waste. Considering both aspects, circular economy and material design, recovery and use of minor metals play an essential role, since their importance for technological applications often goes along with a lack of supply on the world market. Additionally, their ignoble character and low concentration in recycling materials cause an insufficient recycling rate of these metals, awarding them the status of "critical metals". In order to minimize losses and energy consumption, this issue explores concepts for the optimization concerning the interface between mechanical and thermal pre-treatment and metallurgical processes. Such new approaches in material design, structural engineering and substitution are provided in the chapters.